Comparison of tumor surface marking by experienced neurosurgeon versus neuronavigation guidance - Nepal, Pankaj Raj; Rijal, Suman (Journal of Brain and Spine Foundation Nepal, 2020)
Introduction: Accurate flap marking has always been a challenge for neurosurgeons during tumor surgery. The use of neuronavigation has somewhat overcome this problem by allowing the navigation of intraoperative 3D neuroanatomy of the lesion. In this study, we aim to evaluate the percentage discrepancy of tumor surface marking by experienced neurosurgeon versus neuronavigation guidance. Methods: This is a prospective analytical study. Initial surface marking of the tumor was done by experienced neurosurgeon on the basis of sagittal, coronal and axial Magnetic Resonance Imaging films; and later was re-marked using neuronavigation. Photographs of surface markings were taken then comparison was done by plotting marking on the standard graph paper and percentage discrepancies were calculated for every case. Results: Percentage discrepancy ranged from 15 % to 81 % and the mean discrepancy score was 44%. Conclusion: Even in experienced neurosurgeon's hand, flap marking is not always accurate and neuronavigation definitely seems to be an effective tool.